Identidade em performance: um estudo etnográfico sobre as festas de capela no berço da Quarta Colônia de Imigração Italiana/RS - Chiamulera, Márcia (2010)
This thesis addresses the composition of the indentities through the performances produced in the celebrations of chapel in the town of Silveira Martins, located into the Fourth Colony of Italian Imigration in the Rio Grande do Sul. Celebration of chapel is an expression that denote into the own group events that happen in communities from the rural zone, place that have just a space like a little church and a hall, these events happen to honor the patron saint from this comunity. Spaces like these became privilege for the research becouse of limitation of his territory made by italians immigrants during the XIX century, combined to the growth of the memories to rebuild a colonial past and based in a mythical origin. The quest of this work is to map the celebrations of chapel and then take for the analysis five of them, also other two festive events, with the intention to make a local festive table contemplating the daily dimension. Is understood that a festive moment, that symbolize and enlarge the elements of the daily, become a product of it. The fundamentations for this research is based on the discussions about the identity, using mainly concepts about the ethnic and cultural identity contemplating studies about the identity quest front the globalization process. The analysis table is compost for the ethnographic method, as well as, analysis of the performances, mainly corporal, understood as expressive and communicative acts. Although records were used audiovisual bolstered the descriptions and analysis of aspects observed in the field. Thus, it is found that the festivals of Chapel have a multitude of related identity, such as customs, traditions, beliefs, values, habits, modes of knowledge and practices that make up the sense of identity among the group and allow to identify it as belonging to an ethnic identity. These related identity could be observed in the performances of individuals who produce the festival and among its participants. It s possible to say that te celebrations of chapel trigger strategically and resignify belonging to the italian ethnic indentity, highlighting the festival itself as a cultural performance. However, this membership iss seen as contrastive.